2017
DOI: 10.1038/srep45646
|View full text |Cite
|
Sign up to set email alerts
|

Important roles of Vilse in dendritic architecture and synaptic plasticity

Abstract: Vilse/Arhgap39 is a Rho GTPase activating protein (RhoGAP) and utilizes its WW domain to regulate Rac/Cdc42-dependent morphogenesis in Drosophila and murine hippocampal neurons. However, the function of Vilse in mammalian dendrite architecture and synaptic plasticity remained unclear. In the present study, we aimed to explore the possible role of Vilse in dendritic structure and synaptic function in the brain. Homozygous knockout of Vilse resulted in premature embryonic lethality in mice. Changes in dendritic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 31 publications
1
14
0
Order By: Relevance
“…Furthermore, other studies have revealed that changes in dendritic complexity impaired LMC (Freymuth & Fitzsimons, 2017;Lee et al, 2017). Both the microinjection of dme-miR-92b antagomirs and overexpression of crebA in D. melanogaster did result in significant increase of LMC (Bi et al, 2019), further supporting a miRNA-target pathway that regulates the change of LMC in Drosophila induced by Wolbachia infection.…”
Section: Effect Of Wolbachia On Learning and Memory Capacity (Lmc) Inmentioning
confidence: 71%
“…Furthermore, other studies have revealed that changes in dendritic complexity impaired LMC (Freymuth & Fitzsimons, 2017;Lee et al, 2017). Both the microinjection of dme-miR-92b antagomirs and overexpression of crebA in D. melanogaster did result in significant increase of LMC (Bi et al, 2019), further supporting a miRNA-target pathway that regulates the change of LMC in Drosophila induced by Wolbachia infection.…”
Section: Effect Of Wolbachia On Learning and Memory Capacity (Lmc) Inmentioning
confidence: 71%
“…It is plausible that CNK2 serves this purpose for a diverse set of signalling complexes. In this context, the fact that CNK2 also interacts with Vilse/ARHGAP39 (see Supplemental Table 1 and Lim et al 5 ), which has been shown to influence dendritic architecture 42 (see also Nowak et al 43 , for review), may be of relevance. As is the case for TNIK, the interaction with Vilse/ARHGAP39 relies on residues of CNK2 that are present in the C-terminal half of the molecule.…”
Section: Discussionmentioning
confidence: 99%
“…Arhgap39/Porf-2 has been shown to function through regulation of two Rho GTPases, Rac1 and Cdc42. Several investigators have shown that Arhgap39/Porf-2 is a regulator of Rho GTPases and as such plays a role in endothelial cell migration ( Kaur et al, 2008 ), ganglion and axon tracking ( Lundström et al, 2004 ; Hu et al, 2005 ), neural stem cell fate ( Ma and Nowak, 2011 ; Huang et al, 2016 ), and dendritic spine formation ( Lim et al, 2014 ; Lee et al, 2017 ). These studies further link Arhgap39/Porf-2 to angiogenesis, tracheal innervation, and CNS development.…”
Section: Functional Roles and Downstream Effectors ( Table mentioning
confidence: 99%
“…This may reflect variation in expression of mRNA variants 1 and 2, an interesting observation, since they both encode the same protein isoform, but differ in the 5′ UTR. Quite recently, Lee et al (2017) described the effects in hippocampus of a widespread Arhgap39/Porf-2 knockout in mouse forebrain under the direction of the CamKII promoter. These mice show behavioral deficits in learning and memory as measured by Morris water maze and Y-maze performance.…”
Section: Functional Roles and Downstream Effectors ( Table mentioning
confidence: 99%